Developing the model of ecosystem in natural disasters conditions - Zharikova, Maryna (Technology audit and production reserves, 2017)
The spatial model of ecosystem in natural emergency conditions dedicated to decision support tasks solving is described in the paper. The goal of research is decreasing the damage from the natural emergency by means of improving the quality and timeless of forecasting the territorial system dynamics in the natural emergency conditions. The methods of topology, fuzzy sets theories, as well as geoinformation systems and web-technologies were used when performing research. The concept of territorial system in natural emergency conditions in the form of overlaying static and dynamic topological spaces induced by indiscernibility relation is described. Each of the topological spaces allows representing geographical and attributive information about nature conditions, value objects demanding protection against natural emergency, as well as about natural emergency dynamics. The model of natural disaster dynamics in the form of fuzzy dynamic topological space is also described in the paper. This representation of natural disaster model has allowed to provide adaptability to incomplete and inaccurate information. The web-oriented decision support system is created on the base of developed concept and model. The experiments have been conducted, which have shown that the proposed natural emergency model can provide reasonable characteristics in terms of accuracy and speed providing that the space is discretized with the size of cell from 8 m to 18 m.